Factors Associated with the Incidence of Hypertension in the Elderly at the Millenium Clinic in Medan - Maria Haryanti Butarbutar; Zulfikar; Ani Deswita Chaniago; Agnes Ferusgel; Noami Isabella Hutabarat (Science Midwifery, 2021)
Hypertension is a non-communicable disease which is still a global health problem. Hypertension is a condition in which systolic blood pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg on two measurements with an interval of five minutes in a resting state (1). Uncontrolled disease can cause a 7 times greater chance of having a stroke, 6 times greater congestive heart disease, and 3 times greater heart attack is a non-communicable disease which is a very serious health problem today called hypertension.(2). "Silent killer" One of the PTM which is a very serious health problem is hypertension and can be called an iceberg phenomenon. The diagnosis of hypertension is made if a systolic blood pressure (TDS) ≥140 mmHg and / or diastolic blood pressure (TDD) ≥ 90 mmHg is obtained on two measurements at different times (3). Based on WHO data, in 2014 there were around 600 million hypertension sufferers worldwide. The highest prevalence occurs in the African region, which is 30%. The lowest prevalence is in the American region at 18%. In general, men have a higher prevalence of hypertension than women. The highest prevalence occurs in the African region, which is 30%. The lowest prevalence is in the American region at 18%. In general, men have a higher prevalence of hypertension than women (4). The results of the 2018 Riskesdas reported that the prevalence of hypertension in North Sumatra was 45.69% in the age group over 60 years for outpatients. Based on the disease that causes the death of inpatients at the District / City Hospital of North Sumatra Province, hypertension is in the first rank with the proportion of deaths of 27.02% (1,162 people), in the age group ≥ 60 years of 20.23% (1,349 people) ( 5).